AB0950 CORRELATION OF QUANTITATIVE MAGNETIC RESONANCE IMAGING BIOMARKERS AND AXIAL PAIN IN ENTHESITIS-RELATED ARTHRITIS PATIENTS. (June 2019) - Choida, Varvara; Bray, Tim; Radziszewska, Anna; Fisher, Corinne; Ciurtin, Coziana; Sen, Debajit; Hall-Craggs, Margaret
Abstract : Background: Magnetic resonance imaging is increasingly used to diagnose, stratify and monitor inflammation in patients with spondyloarthritis, including young patients with enthesitis-related arthritis (ERA). Recently, there has been interest in the use of quantitative magnetic resonance imaging (qMRI) as an objective method of assessing disease. For example, diffusion-weighted imaging (DWI) and fat fraction (FF) mapping have emerged as biomarkers of oedema and structural damage, respectively, in inflamed bone 1 . However, as yet there are limited data to tie these biomarkers to underlying immunopathology. Objectives: To analyse the relationships between quantitative imaging biomarkers (QIBs), axial pain and serum biomarkers – including 'inflammatory' biomarkers and those reflecting bone turnover - in a cohort of ERA patients. Methods: 28 patients with ERA were prospectively recruited. The hips, sacroiliac joints and lumbar spine were assessed with chemical shift-encoded MRI and diffusion weighted imaging. Quantitative MRI parameters, such as the apparent diffusion coefficient (ADC) and fat fraction (FF) were measured in the sacroiliac joints. Visual scores for inflammation and fat metaplasia were also reported. BASDAI questionnaires were completed. Serum cytokines and bone markers were measured via multiplex bead-based immunoassays (Luminex) and results were available for 14 patients with ERA. Results: The mean visual analogue score for spinal and hip pain (BASDAI Q2) was 3.9 (Table 1 ). There was a correlation between ADCmean and spinal and hip pain (rs=0.393, P=0.043). There was also a negative correlation between FFmean and the above pain score (rs = -0.378, P=0.047). There was a positive correlation between matrix metalloproteinase-3 (MMP-3) levels and FFmean (n=14, rs=0.698, P=0.006). However, the correlation did not reach statistical significance when corrected for multiple testing. Conclusion: The correlation of ADCmean, which increases with increased tissue water/inflammation, with spinal and hip pain suggests that BASDAI Q2 relates to pain of active inflammation. Similarly the inverse correlation of FFmean, which increases with bone healing and reduced inflammation, and BASDAI Q2, would also support this relationship. References: [1] Bray TJP, Bainbridge A, Punwani S, Ioannou Y, Hall-Craggs MA. Simultaneous Quantification of Bone Edema/Adiposity and Structure in Inflamed Bone using Chemical-Shift Encoded MRI in Spondyloarthritis. Magnetic Resonance in Medicine2018Feb;79(2):1031-1042 Disclosure of Interests: None declared